2013
DOI: 10.3892/br.2013.140
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between artificial neural network and Cox regression model in predicting the survival rate of gastric cancer patients

Abstract: Abstract. The aim of this study was to determine the prognostic factors and their significance in gastric cancer (GC) patients, using the artificial neural network (ANN) and Cox regression hazard (CPH) models. A retrospective analysis was undertaken, including 289 patients with GC who had undergone gastrectomy between 2006 and 2007. According to the CPH analysis, disease stage, peritoneal dissemination, radical surgery and body mass index (BMI) were selected as the significant variables. According to the ANN m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 11 publications
(8 reference statements)
0
35
0
Order By: Relevance
“…Although the mean AUC values for both models were far from 0.5, the mean AUC for ANN (0.845) was statistically higher for the LLM (0.744). Some studies also showed that ANN performs as well as or better than traditional statistical models (Kurt et al, 2008;Hashemian et al, 2013;Zhu et al, 2013). However some other studies showed that the traditional model outperforms ANN (Xiang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mean AUC values for both models were far from 0.5, the mean AUC for ANN (0.845) was statistically higher for the LLM (0.744). Some studies also showed that ANN performs as well as or better than traditional statistical models (Kurt et al, 2008;Hashemian et al, 2013;Zhu et al, 2013). However some other studies showed that the traditional model outperforms ANN (Xiang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of ANNs is that these models may rapidly recognize linear, non linear and/or even interaction effects (Zhu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6 key predictors identified by the DT were confirmed by Logistic Regression Likelihood model, which is a tool of choice in medical statistics for binary classification (Zhu et al 2013;Behera et al 2011;Bouwmeester et al 2012). However, the superiority of the DT model is that it was also able to determine dangerous antibody levels, which conventional statistical methods were not able to provide.…”
Section: Practical Significance Of Using Dt For Predictive Modelling mentioning
confidence: 99%
“…Reference [22] reports disparities between treatments effectiveness reported from randomised controlled trials and those achieved in routine clinical practice and population based research which EBM champions may not apply on a patient by patient basis. Thus, in most instances, the knowledge acquired from clinical research studies to design evidence based standards fails to directly address clinical questions regarding what is best for the patient at hand.…”
Section: Emergence Of Evidence Based Medicinementioning
confidence: 99%